Ileitis after colectomy for ulcerative colitis or carcinoma. Issue 3 (March 1994) - Hallak, A; Baratz, M; Santo, M; Halpern, Z; Rabau, M; Werbin, N; Gilat, T
Abstract : An ileitis developing years or months after ileostomy was recognised and described many years ago but has rarely been mentioned since. We describe nine patients with a non-specific preanastomotic ileitis that developed years after colectomy in patients operated on for ulcerative colitis or carcinoma. The disease developed after various types of reconstruction: ileorectal, ileoanal, with or without pouch. The diseased ileum showed inflammation, erosions, ulcerations, and sometimes strictures. The disease course ranged from asymptomatic to severe pain and diarrhoea. No specific cause could be shown. Granulomas, infectious agents or ischaemic changes were not found. The anastomosis was always patent. Three patients have had numerous episodes of intestinal obstruction presumably because of adhesions. Seven of nine patients were female. The response to steroids, 5-aminosalicylic acid preparations, and methotrexate was poor, three patients responded well to azathioprine. The condition is not rare and the cause remains unknown.